Low-Cost Composting for Organic Waste Management in Urban Areas: A Systematic Review (OCEM Journal of Management, Technology & Social Sciences, 2026)
This study explores low-cost composting methods for organic waste management in urban areas, specifically Windrow composting, Takakura composting, and Vermicomposting. While many studies discuss general composting, few reviews have comparatively analyzed the technical, economic, and environmental feasibility of these specific methods for the developing cities. A systematic literature review was con- ducted using the Scopus, Google Scholar, Science Direct, and Research Gate databases for the period 2015–2025, with the keywords: “low-cost composting,” “windrow composting,” “takakura composting,” and “vermicomposting.” Results indicate that while Windrow composting is wellsuited for large-scale municipal operations, it requires a larger processing time (45-90 days) and significant land buffers to mitigate greenhouse gas emissions.In contrast, Takakura composting is most suitable for high-density urban settings, offering a rapid 10-14 days decomposition period, 40-50% waste volume reduction, and emission reductions up to 132 tCO2-eq/day in city-wise applications. Vermicomposting produces the highest economic value product (approx. $85/tonne or 10,000 BDT/Mt) but is constrained by strict temperature requirements (18-30°C) and longer duration (45-60 days). Ultimately, this review concludes that Takakura composting is the most viable solution for spaceconstrained households due to its speed and compactness. A hybrid approach– integrating Takakura bins with centralized Windrow facilities–can be used to maximize urban waste diversion and environmental sustainability. Further research on integrated approaches is recommended to maximize the benefits of these composting techniques in urban settings.